Customized Nutritional Intervention to Improve Body Composition, Macronutrient Intake, and Nutritional Behavior in Moderate to Severe Obese Children and Adolescents (P21-063-19). (13th June 2019) - Kim, Jieun; Kim, YoonMyung; Park, Kyung-Hee; Jang, Han Byul; Lee, Hye-Ja; Park, Sang Ick; Lim, Hyunjung
Abstract: Objectives: Evidence-based customized nutritional interventions are required for effective treatment of moderately-severely obese children and adolescents. Methods: Eligible participants who agreed to participate in the intervention program provided informed consent. Customized nutritional intervention was implemented for each participant based on a nutrition care process (NCP) model. Sociodemographic assessment, anthropometrics, biochemical data, health- and dietary-related behaviors, and dietary intake of the study subjects were assessed at baseline and follow-up. All participants engaged in 30-minute nutritional sessions on a monthly basis. Results: One hundred three [mean age: 12.4 years, severely obese: n = 69(67%)] children and adolescents were assessed at baseline. After 16 weeks, there were significant improvements in body composition [BMI (−0.8 ± 0.9, P < 0.05), BMI z-score (−0.3 ± 0.2, P < 0.001), body fat (kg) (−1.3 ± 2.1, P < 0.05), and body fat (%)(−1.5 ± 1.9, P < 0.05)] as well as macronutrient intake [total energy intake (kcal)(−563.7 ± 656.8, P < 0.05), energy (%)(−26.5 ± 30.0, P < 0.05) and fat (g)(−28.3 ± 40.6, P < 0.05)] in the adherent group than the non-adherent group. The stage of change according to the transtheoretical model (TTM) was higher in both groups after the intervention ( P < 0.001). Conclusions: Our customized nutritional intervention resulted in improvements in body composition, macronutrient intake, and nutritional behavior in adherent moderately-severely obese children and adolescents. These results highlight the positive effects of an evidence-based approach as a multidisciplinary intervention for people-centered nutritional care and weight management. Funding Sources: This study was funded by Korea Centers for Disease Control and Prevention Grant 2015-ER6401-00.